The first European Portuguese elderly speech corpus - Hämäläinen, A.; Moreira, F. P.; Dias, J.; Júdice, A.; Freitas, J.; Pires, C.; Teixeira, V.; Calado, A.; Daniela Braga (Proceedings das Jornadas en Tecnologia del Habla and Iberian SLTech Workshop (IberSPEECH 2012), 2012)
Currently, available speech recognisers do not usually work well with elderly speech because the underlying acoustic models have typically been trained using speech collected from younger adults only. To develop speech-driven systems capable of successfully recognising elderly speech, a sufficient amount of elderly speech data is needed for training the acoustic models. This paper describes an elderly read speech data collection effort carried out in Portugal from the autumn of 2010 until the spring of 2012, applying a low-cost proctored data collection methodology using our in-house data collection platform, Your Speech. The resulting corpus of Portuguese elderly speech contains almost 90 hours of pure speech (speech with silences excluded). The transcriptions for about half of the data have already been manually verified and annotated for noises and disfluencies.